EFISIENSI ASURANSI JIWA SYARIAH: PENDEKATAN DATA ENVELOPMENT ANALYSIS - Darmawan, Rifki; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research was intended to measure the efficient value of Sharia life insurance in Indonesia with the span of 2018-2021. The data used in this study was 10 Sharia life insurance companies obtained from financial reports each company. The measuring instrument used in this study is a non-parametric type using the Data Envelopment Analysis (DEA) method. The results obtained in this study are that Sharia Life Insurance companies in Indonesia have not reached an efficient level. That's supported by an average technical efficiency value (TE) of 0.72 %, pure efficiency (PTE) of 0.81 %, and scale efficiency (ES ) of 0.87%.